Priority hybrid and EEF uplink scheduling algorithm for IEEE 802.16E - Oad, Aneel (2013)
Worldwide interoperability for Microwave Access (WiMAX) is based on the IEEE 802.16 standard. The IEEE 802.16-2004 standard (i.e. Fixed WiMAX) provides specification for the Medium Access Control (MAC) and Physical (PHY) layers for WiMAX. A critical part of the MAC layer specification is scheduling, which resolves contention for bandwidth and determines the transmission order of users. In this research the focus is on the WiMAX uplink traffic scheduling in the Point to Multipoint (PMP) mode. In this research, two algorithms tailored at enhancing the performance of hybrid algorithms in the WiMAX domains have been designed and developed. The spectrum of constraints which have been extracted from the researched hybrid algorithm includes the static nature by which priorities are assigned and maintained during the entire duration of a transmission time. The second constraint is embedded within the EDF scheduling algorithm and the perseverance of pursuing deadline associated weightages. In this research, the introduction of a versatile and flexible computing threshold has been developed. The second contribution of this research is the reengineering of the EDF scheduling algorithms. The dominance of the pre-stipulated deadline is indeed acknowledged in the proposed and developed enhanced EEF algorithm. The simulation results indicate that legacy algorithms are not suitable for the multi-class traffic systems of WiMAX. This is because these algorithms do not explicitly incorporate the WiMAX QoS parameters into their mechanisms. Extensive discrete – event simulation experiments have been done for the purpose of performance analysis. The performance metrics used are average throughput, average delay, missed deadline ratio and average queue size utilization ratio. The acquired results have proven that the proposed algorithms have successfully enhanced the legacy hybrid and the deadline based algorithm.